2022
DOI: 10.1111/maps.13818
|View full text |Cite
|
Sign up to set email alerts
|

Artificial weathering of an ordinary chondrite: Recommendations for the curation of Antarctic meteorites

Abstract: Meteorites are prone to errestrial weathering not only after their fall on the Earth's surface but also during storage in museum collections. To study the susceptibility of this material to weathering, weathering experiments were carried out on polished sections of the H5 chondrite Asuka 10177. The experiments consisted of four 100-days cycles during which temperature and humidity varied on a twelve hours basis. The first alteration cycle consisted of changing the temperature from 15 to 25 °C; the second cycle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 73 publications
1
6
0
Order By: Relevance
“…Within the Atacama chondrites, metal and sulfide grains are the main phases that show significant signs of alteration by terrestrial fluid percolation, suggesting that silicates and calciumaluminum-rich inclusions (CAIs) likely preserve their original O isotopic compositions acquired upon condensation/crystallization. The limited extent of the alteration of silicates and CAIs is also supported by recent weathering experimental results in chondrites (Van Ginneken et al, 2022). Applying a range of temperatures and humidity levels on polished sections of the H5 chondrite Asuka-10177, the experiments revealed extensive weathering of the Fe-Ni metal grains, but only a minor alteration of troilite and no evidence of mafic silicate alteration.…”
Section: Chondrites In the Atacama Desert And Other Collectionssupporting
confidence: 62%
See 1 more Smart Citation
“…Within the Atacama chondrites, metal and sulfide grains are the main phases that show significant signs of alteration by terrestrial fluid percolation, suggesting that silicates and calciumaluminum-rich inclusions (CAIs) likely preserve their original O isotopic compositions acquired upon condensation/crystallization. The limited extent of the alteration of silicates and CAIs is also supported by recent weathering experimental results in chondrites (Van Ginneken et al, 2022). Applying a range of temperatures and humidity levels on polished sections of the H5 chondrite Asuka-10177, the experiments revealed extensive weathering of the Fe-Ni metal grains, but only a minor alteration of troilite and no evidence of mafic silicate alteration.…”
Section: Chondrites In the Atacama Desert And Other Collectionssupporting
confidence: 62%
“…These variations depend on the distance from the Pacific Ocean, which can generate dense coastal fog and topographic elevation, which controls the precipitation rate among the different morphotectonic units (Boy et al., 2022). Experimental studies show that metal corrosion in OCs is mostly controlled by thermoclastic weathering produced by temperature fluctuations during day/night and high level of humidity (Van Ginneken et al., 2022). Both are common factors in the Atacama Desert, with slightly major level of humidity in CR.…”
Section: Dcas In the Atacama Desertmentioning
confidence: 99%
“…(this volume) also found terrestrial sulfates occurring in areas outside the fusion crust within the P30552 section of Winchcombe. Other studies have shown early weathering occurs in meteorites (e.g., Van Ginneken et al., 2022); however, these observations emphasize that terrestrial alteration occurs rapidly and that even meteorites observed to fall are not exempt. It also suggests that fusion crust provides an opportunity to demonstrate the terrestrial origins of alteration products.…”
Section: Discussionmentioning
confidence: 85%
“…According to Mittlefehldt and Lindstrom (1991), melting of ice in Antarctica can trigger sample alteration following chemical leaching as demonstrated by the loss of Ca‐phosphates in eucrites from Antarctic samples, in line with our observations for cracks in Antarctic chondrites. Rain or humidity is known to trigger a similar mechanism in hot deserts (e.g., Al‐Kathiri et al., 2005; van Ginneken et al., 2022). During the residence of meteorites in Antarctica, hot deserts, or anywhere else on the Earth, fluids such as melting ice or rain pass through the interior of a meteorite following any physical weaknesses, cracks, or grain boundaries.…”
Section: Discussionmentioning
confidence: 99%
“…As falls are usually collected shortly after the fall events, they are in general significantly fresher than finds, as the latter have been subjected to weathering to various degrees during their terrestrial residence (roughly of the order of tens of kyr in most hot deserts and up to a few Myr in Antarctica and Atacama: e.g., Al‐Kathiri et al., 2005; Drouard et al., 2019; Nishiizumi et al., 1989; Zekollari et al., 2019). Terrestrial weathering may change the original mineralogy and chemical compositions of meteorites due to oxidation, hydration, and so on, that is, the alteration to phases that are more stable at the Earth's surface depending on environmental factors such as humidity and temperature (e.g., Bland et al., 2006; Koeberl & Cassidy, 1991; Lee & Bland, 2004; van Ginneken et al., 2022). To evaluate the degree of weathering for finds, two classification systems are commonly applied: the ABC index for Antarctic meteorites and a scale with seven categories from W0 to W6 used mainly for ordinary chondrites (Antarctic Meteorite Newsletter, NASA; Meteorite Newsletter, NIPR; Bland et al., 2006; Gooding, 1989; Wlotzka, 1993).…”
Section: Introductionmentioning
confidence: 99%